Nghiên cứu thành phần hóa học cây song môIitàu (Miliusa sinensis Finet et Gagnep.), họ Na (Annonaceae). Phần I - Các hợp chất flavonoit - Thanh Thủy, Trần Thị; Quân, Trần Đức; Hoàng Anh, Nguyễn Thị; Sung, Trần Văn (Vietnam Journal of Chemistry, 2014)
Four methoxy flavanones: pinostrobin (1), 5-hydroxy-7,4’-dimethoxy flavanone (2), 5-hydroxy-6,7-dimethoxy flavanone (3) and 5-hydroxy-7,8-dimethoxy flavanone (4) were isolated from the n-hexane extract of Miliusa sinensis. Their structures were elucidated by analysis of MS and NMR spectra and comparison with the published data.